Qualidade da àgua de um córrego em àrea agrícola onde é usado composto orgânico de resíduos animais e vegetais - Saran, Luciana Maria [UNESP]; Meneghine, Aylan Kener [UNESP]; Célico, Amanda Schimidt [UNESP]; Pinheiro, Daniel Guariz [UNESP]; Alves, Lucia Maria Carareto [UNESP] (FapUNIFESP (SciELO), 2017)
Organic compost from biomass residues constitutes a viable alternative for partial or total replacement of mineral fertilizers for growing vegetables. This study evaluated the effects of compost on the water quality of a stream used mainly for irrigation of agricultural crops cultivated in nearby soil that has been treated with organic compost produced by carcasses, animal and vegetable waste for the last ten years. We sampled water biannually for two years, 2013 and 2014, from five locations along the stream. Physical variables and some chemical variables were analyzed. We also analyzed the total number of coliforms (Escherichia coli). Bacterial populations were compared by carbon substrate consumption. Total phosphorus contents in the samples from 2014 exceeded 0.1 mg L-1. The concentrations of other chemical species analyzed and the results for the physical variables were in accordance with the expected values compared with national and international water quality standards. The environment showed differential carbon source consumption and a high diversity of microorganisms, but our results did not show any evidence that the applied compost is changing the microbial population or its metabolic activity. This study shows that the use of the organic compost in agricultural areas seen does not negatively influence the quality of surface water in the study area. These results are important because the process of composting animal and vegetable waste and the use of compost obtained can be an alternative sustainable for adequate destination of these wastes.
Freshwater quality of a stream in agricultural area where organic compost from animal and vegetable wastes is used
Keywords: Agriculture; Carcasses and animal waste; Composting; EcoPlate; Surface water